Rancang Bangun Smart Doorbell Berbasis Internet of Things (IoT) Menggunakan ESP32-CAM via Telegram - Prakoso, Satrio Bagus (YASIN, 2025)
Home security remains a major concern, particularly due to the limitations of conventional doorbells that provide only audible alerts without visual support or activity recording. This condition increases the risk of unauthorized access, complicates monitoring efforts, and results in a lack of documentation during criminal incidents. This study aims to design and develop an Internet of Things (IoT)-based Smart Doorbell using the ESP32-CAM module, integrated with the Telegram application for notification and monitoring purposes. The methodology includes hardware design involving the ESP32-CAM, sensors, and a notification system, as well as performance testing based on notification speed, image quality, and the reliability of two-way communication. Testing was conducted under various network and lighting conditions to obtain comprehensive results. The findings indicate that the system is capable of sending real-time notifications with low average delay, producing sufficiently clear images in both bright and low-light settings, and supporting two-way communication between users and visitors. The system is also equipped with an automatic activity recording feature at the door, contributing to enhanced home security. Thus, the ESP32-CAM-based Smart Doorbell integrated with Telegram has proven effective in improving both the security and convenience of users within a smart home environment.